Notes on the genera and species in the mealybug tribe Serrolecaniini Shinji (Hemiptera: Coccoidea: Pseudococcidae) from China with description of a new species - Wu, San-An; Lu, Yuan (Zootaxa, 2012)
The eight species in five genera belonging to the tribe Serrolecaniini recorded from China are discussed, including a newspecies Serrolecanium ferrisi Wu & Lu (previously misidentified as S. tobai (Kuwana) or S. indocalamus Wu) and a newcountry record for Serrolecanium kawaii Hendricks & Kosztarab. A key to species belonging to the tribe Serrolecaniini now known from China is included and illustrations are provided to the adult female of all species found in China.